AKAR KORUPSI - George Kirchberger (Institut Filsafat dan Teknologi Kreatif Ledalero, 2016)
The author of this article starts from the fact that in Indonesia, as in many other countries, corruption is rapidly escalating, and seemingly is extremely difficult to eradicate. And so the author questions the root of corruption. From an ethical perspective, corruption is clearly categorised as a social sin. In the Catholic view, sin is rooted in what is known as “original sin”. Making use of the study of Eugen Drewermann, the author describes the root of sin as suspicion of God, an attitude that is no longer convinced that God can be relied upon as source of life and basic guarantor of human life. Thus, humans become convinced that they themselves must guarantee the foundation of their existence. To achieve this, humans seek power, property and wealth as the source of apparently guaranteeing the basis of their life. However, humans know in their heart that death is going to take everything away, and so become avaricious and feel that they never own enough to secure themselves. Because of this sinful mechanism, corruption will never be overcome as long as the underlying distrust is not overcome through conviction. In order to oppose corruption, the Church needs to attempt to plant in the hearts of humanity confidence that God can be relied upon as the foundation and guarantor of life. Only then can humans be freed from the necessity of guaranteeing life by their own efforts.